2014
DOI: 10.1126/science.1251423
|View full text |Cite
|
Sign up to set email alerts
|

Greater Sensitivity to Drought Accompanies Maize Yield Increase in the U.S. Midwest

Abstract: A key question for climate change adaptation is whether existing cropping systems can become less sensitive to climate variations. We use a field-level data set on maize and soybean yields in the central United States for 1995 through 2012 to examine changes in drought sensitivity. Although yields have increased in absolute value under all levels of stress for both crops, the sensitivity of maize yields to drought stress associated with high vapor pressure deficits has increased. The greater sensitivity has oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

42
639
5
6

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 891 publications
(692 citation statements)
references
References 23 publications
42
639
5
6
Order By: Relevance
“…Modeling studies have shown that increases in WUE are required to realize theoretical maximum yields in regions where crop production is constrained by water availability (Delucia et al, 2014). Additionally, research has shown that as maize yields have increased, the sensitivity of maize to drought has also increased (Ort & Long, 2014;Lobell et al, 2014). Therefore, comparing the ET, WUE, and droughttolerance of bioethanol feedstocks may help inform decisions on future feedstock implementation.…”
Section: Chapter 1 Water-use-efficiency Of Sorghummentioning
confidence: 99%
See 2 more Smart Citations
“…Modeling studies have shown that increases in WUE are required to realize theoretical maximum yields in regions where crop production is constrained by water availability (Delucia et al, 2014). Additionally, research has shown that as maize yields have increased, the sensitivity of maize to drought has also increased (Ort & Long, 2014;Lobell et al, 2014). Therefore, comparing the ET, WUE, and droughttolerance of bioethanol feedstocks may help inform decisions on future feedstock implementation.…”
Section: Chapter 1 Water-use-efficiency Of Sorghummentioning
confidence: 99%
“…Limited water availability associated with climate change may constrain maize yields in rain-fed systems (Ort & Long, 2014), and research demonstrates an increase in the sensitivity of maize to drought, in the rainfed, Midwest US (Lobell et al, 2014). A potential adaptation strategy is to grow productive yet drought tolerant bioethanol feedstocks with high water-use-efficiency (WUE; Enciso et al, 2015), defined as the ratio of cumulative biomass produced to total water lost through evapotranspiration (ET; the sum of transpiration and evaporation).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drought and nutrient stress are primary global constraints to agricultural productivity (Tilman et al 2002;Lynch 2007;Lobell et al 2014). Climate change is projected to intensify the importance of crop water stress as a result of altered precipitation patterns, and soil degradation (Tebaldi and Lobell 2008;Brisson et al 2010).…”
mentioning
confidence: 99%
“…Regression analyses usually consider the effect of temperature and precipitation on crop yields (Lobell and Field, 2007;Nicholls, 1997;Corobov, 2002) and its derived composites, such as growing degree days (GDD) (Lobell et al, 2011), evapotranspiration (Blanc, 2012), and drought indices (Lobell et al, 2014;Blanc, 2012;Carter and Zhang, 1998). Some studies control for alternative effects, such as cloud cover (You et al, 2009); sources of water availability, such as proximity to streams (Blanc and Strobl, 2014) and dams (Strobl and Strobl, 2010;Blanc and Strobl, 2013); management strategies, such as fertilizer application (Cuculeanu et al, 1999) or changes in planting dates (Alexandrov and Hoogenboom, 2000); and technological trends (Lobell and Field, 2007).…”
Section: Introductionmentioning
confidence: 99%